Les plantes envahissantes en Polynésie française : un exemple d’approche de la complexité en science de l’environnement - Sébastien Larrue (VertigO)
Introduced from the beginning of the 20th century, most invading plants in French Polynesia constitute a real challenge for the biodiversity preservation. Today we are faced with a serious problem, preventing the spread of species which invade, mainly in Tahiti, many ecological niches. Such an invasion is not surprising, it simply fits with the model of ecological successions in an insular environment. But, above all, the geographic diversity of origin of these introductions, accelerating during the last decades, reflects the opening of French Polynesia to globalization and the evolving representation of plants in the Polynesian society.Thus the question of invading plants does not refer only to “natural sciences”, it concerns also the social sciences. Social representations of species and forest spaces as well as local politics are inherent components of that set of themes. Moreover, the proposed text shows that complexity, in the original sense, is central to the subject. This complexity shows clearly a problem of methodology. It reflects the role played today by geography in the environmental sciences.